Textbook of Energy Balance, Neuropeptide Hormones, and Neuroendocrine Function (Springer International Publishing, 2018)
This textbook presents for the first time a comprehensive body of the latest knowledge in the field of neuropeptides and their action on energy balance. It contains a detailed and comprehensive account of the specific hypothalamic peptides in regards to their roles in energy balance, food intake control and co-morbidities, to better understand the patho-physiology of obesity. The textbook includes an examination the history of the evolution of human society from a thin to the obese phenotype and, within that context, how modern society habits and industrial food production did not respect the evolutionary trait resulting in changes in the energy balance set point. It provides a novel conceptualization of the problem of obesity when considering the biochemistry of peptide hormones and entertaining novel ideas on multiple approaches to the problems of energy balance, as well as demonstrates and explains why alterations in pro-hormone processing are paramount to understand metabolic disease. This text is excellent material for teaching graduate and medical school courses, as well as a valuable resource for researchers in biochemistry, cell, and molecular biology, neuroscientists, physician endocrinologists, and nutritionists.